HGG-54. CLK1 aberrant splicing in pediatric high-grade gliomas disrupts key oncogenic transcriptional programs. (3rd June 2022) - Naqvi, Ammar; Ennis, Brian; Jin, Run; Gaonkar, Krutika; Foster, Jessica; Conkrite, Karina; Rathi, Komal; Kraya, Adam; Sonawane, Poonam; Madsen, Peter; Storm, Phillip; Resnick, Adam; et al.
Abstract: While much of the somatic coding variation underlying the oncogenic transformation of pediatric high-grade gliomas (HGGs) has been profiled, transcriptional splicing programs of these tumors remain under-explored. Here, we characterize aberrant alternative splicing in pediatric midline HGGs (n = 84). We identified 19, 275 recurrent and significant (20% change from control, P < 0.05, FDR < 0.05) aberrant splicing events in 8, 587 genes compared to non-diseased brainstem controls. Of those, 27% (n = 5, 157) resulted in either a gain or loss of a known protein functional site within 3, 294 genes. We prioritized splice variants affecting targetable kinases and found that mRNAs encoding CDC-like kinase 1 (CLK1), a known modulator of master splicing regulators, exhibit significantly increased exon 4 inclusion in midline HGGs. This leads to a gain of two known phosphorylation sites in CLK1, increased CLK1 protein expression and hyper-phosphorylation of Serine-rich splicing factors. To assess the impact of this event, we performed differential splicing and expression analyses, comparing tumors with the highest (n= 5) and lowest (n = 5) exon 4 inclusion. We discovered 3, 037 genes to be differentially up-regulated in high exon 4 inclusion tumors with an enrichment of cancer-related pathways, including DNA repair, mitotic spindle, myogenesis and EMT. We next integrated these gene signatures with protein-protein interaction networks of kinase and transcription factors and show that increased CLK1 exon 4 inclusion disrupts critical regulatory networks, such as those involving FOXM1, which is implicated in cell cycle and proliferation processes. In summary, we describe aberrant splicing in pediatric HGGs as an additional mechanism that could drive tumorigenesis. Future work will focus on molecular validation and therapeutic targeting of CLK1 in available HGG models. Characterizing tumor-specific splicing variation has the potential to open new therapeutic strategies and understand mechanisms of treatment resistance in children with central nervous system tumors.